Nurturing layers - Hamada, Natalie (Taideyliopiston Kuvataideakatemia, 2022)
The Masters of Fine Arts thesis project consists of an artistic component, which was shown in two parts: the annual MFA degree show Kuvan Kevät 2021 (12.5 - 31.6.2021, Exhibition Laboratory, Helsinki) and the solo show Illuminated Tales (10.12.2021 - 02.01.2022, Project Room, Helsinki). Both exhibitions adopted silkscreen printing technique as the main medium for expression. They explored the theme of the different facets of emotional life within figurative contemporary artworks. The other part of the thesis project is the written supporting text as seen here. Loneliness was the central theme of my work Diary Thoughts in Kuvan Kevät 21. I had arrived in Helsinki during the first lockdown period of COVID-19 and had little contact with other students or people in the community. The work I developed reflects the feelings of isolation. The second exhibition was in the front room of the Project Room titled Illuminated Tales and acted as a continuation of Diary Thoughts. The images reflected on how emotional experiences refer to questions regarding identity and belonging. Both exhibitions contained medium and large scale silkscreen digital collaged works in a pictorial narrative way. The written component Nurturing Layers aims to reflect on and document the artistic investigation, process and methodology. It contains a description of each artwork, the preparations of the two exhibitions’ artistic work and includes photographic documentation.
Keywords: fi=taidegrafiikka|sv=konstgrafik|en=Printmaking|